Partial trisomy of short arm of chromosome 6: a case due to paternal balanced translocation - Yüksel, Memnune; Jones, Larry A.; Tayşi, Kutay; Henry, Catherine G. (The Turkish Journal of Pediatrics, 1980)
A partial trisomy for the distal segment of the short arm of chromosome 6 (6p22→6pter) was found in an infant with psychomotor retardation, multiple congenital anomalies and dysmorphic features. The phenotypically normal father had a balanced translocation between the long arm of chromosome 5 and the short arm of chromosome 6. Distinct similarities of the clinical features observed in 10 patients with the partial trisomy of the short arm of chromosome 6 allowed the delineation of the syndrome of 6p trisomy. The correlation of the clinical features of the patients reported here with their cytogenetic findings suggest that the main clinical features of this newly recognized chromosomal syndrome are due to the excess of a specific short arm segment of chromosome 6 that includes bands p23 and/or p25.